Spacer Organic Cation Engineering for Quasi‐2D Metal Halide Perovskites and the Optoelectronic Application. Issue 7 (23rd April 2022) - Zhou, Ning; Zhou, Huanping
Abstract : Recently, organic and inorganic halide perovskites are one of the most popular semiconductors owing to their enormous potential for optoelectronic application, such as photovoltaics (PV), light‐emitting diode (LED), photodetector, and so on. The photoelectric conversion efficiency of 3D organic–inorganic hybrid perovskite solar cells has increased rapidly; however, the commercialization of the related devices is largely hampered by the poor stability of perovskite materials under environmental stress. Compared to 3D halide perovskites, quasi‐2D (Q‐2D) perovskites have improved moisture stability and less tendency for ion migration, which offers a new approach to stabilize perovskite‐based optoelectronic devices. Furthermore, Q‐2D hybrid perovskites have diverse structures with different quantum confinement and dielectric confinement characteristics, which enables the fine‐tuning of their optoelectronic properties through structure engineering. Depending on the different structures of spacer organic cations, the Q‐2D perovskite structure mainly includes Ruddlesden−Popper (RP) phase structure, Dion−Jacobson (DJ) phase structure, and alternating cation in the interlayer space (ACI) phase structure. In this review, the state‐of‐the‐art in Q‐2D perovskites is discussed based on their structural engineering, and an overview of PV and LEDs applications is provided. Finally, a brief outlook with respect to the development of Q‐2D perovskite materials, as well as advanced device, is provided. Abstract : Herein, the Q‐2D perovskites based on their structural engineering, including Ruddlesden–Popper (RP) phase structure, Dion–Jacobson (DJ) phase structure, and alternating cation in the interlayer space (ACI) phase structure are discussed, and an overview on the PV and LEDs applications is provided. Finally, a brief outlook with respect to the development of Q‐2D perovskite materials, as well as advanced device is provided.